Pre-hydrated bentonite anti-seepage material and preparation process thereof
The calcium-based bentonite is modified by modifying the vinyl carbonate intercalation and organic composite components to expand the layer spacing and enhance the water locking ability, which solves the problems of poor water absorption and easy eluting of calcium-based bentonite, and achieves efficient water absorption and water locking performance.
Patent Information
- Application Number
- CN202510756639.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-09
- Publication Date
- 2025-07-04
- Estimated Expiration
- 2045-06-09
AI Technical Summary
The existing calcium-based bentonite anti-seepage materials have poor water absorption and expansion properties, and the small molecule intercalation agent is easy to eluate after the intercalation modification, which affects its water locking performance and anti-seepage effect.
The calcium-based bentonite is modified by vinyl carbonate interlayer, and the layer spacing is expanded by organic composite components, and the polyethylene glycol repeat segment is introduced between the montmorillonite layers to capture water molecules. Combined with acylation modification, it increases the migration resistance of the interlayer agent to form a stable complex structure.
It improves the water absorption and water locking ability of calcium-based bentonite, reduces the elution risk of intercalation agent, the water absorption rate is ≥5.2, and the water retention rate is ≥63.7%, significantly improving the performance of anti-seepage materials.
Smart Images

Figure CN120247524A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the technical field of bentonite anti-seepage materials. More specifically, it relates to a pre-hydrated bentonite anti-seepage material and its preparation process. Background Art
[0002] As an important non-metallic mineral material, bentonite has important application value in the field of engineering anti-seepage due to its unique expansibility, excellent adsorption performance and good bonding characteristics. Its core component, montmorillonite, can adsorb several times its own volume of water and swell in water to form a dense gel layer, effectively blocking water penetration. According to types, bentonite anti-seepage products mainly include natural bentonite powder, sodium-based bentonite waterproof blankets, pre-hydrated bentonite anti-seepage materials, etc.; among them, pre-hydrated bentonite anti-seepage materials show significant advantages in engineering applications based on their mature industrial production technology and high construction performance.
[0003] The preparation process of pre-hydrated bentonite anti-seepage materials mainly includes: mixing bentonite and water in a specific ratio, adding a binder to form a homogeneous pre-hydrated slurry, and then after being coated with geotextile, obtaining the finished product through molding by pressing; among them, sodium-based bentonite is an ideal bentonite raw material, but due to its high price, it restricts its large-scale production and application; while calcium-based bentonite is low in price, but affected by the high-valent calcium ions in its structure, its layer spacing is relatively narrow, and the water absorption and swelling properties of the directly prepared pre-hydrated bentonite anti-seepage materials are often not excellent.
[0004] The Chinese patent application document with the publication number of CN117819561A discloses modified bentonite, its preparation method, bentonite-based anti-seepage materials and applications. In the solution, sodium hexafluorosilicate, etc. are used as intercalating agents. After adding water and mixing with bentonite to obtain a mixed homogeneous slurry, and then through freezing treatment, modified bentonite is obtained; through the way of intercalation combination, the layer spacing of bentonite can be increased, and finally the swelling and anti-seepage properties of bentonite can be improved.
[0005] Although the above-mentioned application document can improve the swelling and anti-seepage properties of the prepared anti-seepage materials through the way of intercalation combination, the intercalating agents used are mainly small molecules. After intercalation treatment, the small molecule intercalating agents are easily eluted by the external environment, and the water locking performance of the modified bentonite also needs to be improved; therefore, it is necessary to find a pre-hydrated bentonite anti-seepage material that takes into account the water absorption and swelling properties and at the same time reduces the risk of elution of small molecule intercalating agents. Summary of the Invention
[0006] In order to further improve the water absorption and water locking ability of calcium-based bentonite anti-seepage materials and at the same time reduce the risk of elution of small molecule intercalating agents after intercalation modification, this application provides a pre-hydrated bentonite anti-seepage material and its preparation process.
[0007] In a first aspect, the present application provides a preparation process for a pre-hydrated bentonite anti-seepage material, which is obtained by mixing and processing raw materials including the following parts by mass: 80-90 parts of calcium-based bentonite, 10-12 parts of a binder, 5-8 parts of an organic composite component, and 3-5 parts of ethylene carbonate; the preparation steps include the following: Take calcium-based bentonite, crush it and then sieve it, then add water for dispersion, adjust the pH, then add ethylene carbonate, raise the temperature and stir for treatment, then add the organic composite component, continue the treatment, then filter to obtain the solid part, add the binder, and then carry out mixing, film covering and then molding treatment, and obtain the product after cooling; Among them, the preparation steps of the organic composite component include the following: [S01] Take oligo-polyethylene glycol, dissolve it in a mixed solvent, then dropwise add an acylating reagent, react in the dark, then carry out reduced pressure filtration, take the liquid phase and adjust the pH, and successively carry out precipitation separation and rotary evaporation to obtain acylated polyethylene glycol; [S02] Take acylated polyethylene glycol, disperse it, then add p-toluenesulfonyl chloride, react and then carry out rotary evaporation, then redissolve it, add phthalimide, dropwise add potassium hydroxide solution, raise the temperature for treatment, then remove the solvent, redissolve it again, add hydrazine hydrate, carry out reflux reaction, and obtain the product after purification.
[0008] By adopting the above technical solution, organically intercalated modified bentonite can be obtained. As a small molecule organic intercalating substance, ethylene carbonate can be inserted into the montmorillonite structure layer of bentonite, and by virtue of the carbonyl group and ether oxygen group in its molecular structure, it combines with the Ca 2+ cation between the montmorillonite layers, increasing the layer spacing; the organic composite component can enter the montmorillonite layers through the enlarged interlayer structure and play a role; in the structure of the organic composite component, the polyethylene glycol repeating segments can be used to capture water molecules, confine the water molecules in the montmorillonite layer structure, and improve the water locking ability; and after being modified with terminal amino groups, the lone pair electrons of the introduced amino nitrogen atoms can combine with Ca 2+ and other metal cations on the montmorillonite through coordination to form a ternary complex stable structure of "montmorillonite layer board - metal cation - organic composite component". In the complex structure, the organic composite component is distributed in a "comb" shape between the montmorillonite layer boards; at the "comb" tail part, the acylated grafted short branched chain structure groups can increase the migration resistance of the intercalating agent ethylene carbonate in the montmorillonite layers through the steric hindrance of the branched alkyl structure, and ethylene carbonate is less likely to be separated from the layers by the water migration effect, thereby reducing the risk of elution of the intercalating agent.
[0009] Preferably, the temperature-raising and stirring treatment is: set the temperature at 60-80 °C, adjust the stirring speed to 75-100 rpm, and stir for 2-4 h.
[0010] By adopting the above technical solution, the small molecule intercalating agent ethylene carbonate can intercalate and combine between the montmorillonite layers of bentonite. The heating and stirring treatment is beneficial to increasing the contact area between montmorillonite and ethylene carbonate and improving the efficiency of ethylene carbonate molecules diffusing into the interlayer domain.
[0011] Preferably, in the step [S01], the mixed solvent is obtained by mixing dimethyl sulfoxide and triethylamine in a volume ratio of (20 - 25):1.
[0012] Preferably, in the step [S01], the preparation steps of the oligo-polyethylene glycol include: taking ethylene glycol monomer, dissolving it, adding an alkali catalyst, stirring and mixing, then transferring it to a reaction kettle, and then dropwise adding ethylene oxide, purging with nitrogen, heating and reacting, adjusting the pH after pressure release, then cooling down, filtering with an ion exchange resin, and dehydrating to obtain oligo-polyethylene glycol; The heating reaction is: raising the system temperature to 100 - 110 °C, adjusting the pressure to 2 - 2.3 MPa, and treating for 6 - 8 min; The mass - volume ratio of the addition of the ethylene glycol monomer, alkali catalyst, and ethylene oxide is 5 ml:(0.2 - 0.3) g:(17.1 - 18.4) ml.
[0013] By adopting the above technical solution, polyethylene glycol with a short - chain structure can be obtained. In the polymerization reaction, the ethylene glycol monomer is used as the initiator. Through heating treatment and catalysis by an alkali catalyst, the ring - opening of ethylene oxide is initiated to form an oxygen anion intermediate, and the intermediate continues to react to obtain a polyethylene glycol chain - growth structure. By adjusting the reaction time and quenching the reaction in time by adjusting the pH, oligo - polyethylene glycol can be obtained.
[0014] Preferably, the alkali catalyst is a supported K2O / ZrO2 catalyst, and the preparation steps are as follows: Taking zirconium oxychloride octahydrate, adding sodium hexametaphosphate and potassium nitrate, dispersing, then dropwise adding ammonia water to adjust the pH, standing, taking the precipitate, drying, and then calcining to obtain it.
[0015] By adopting the above technical solution, after zirconium oxychloride octahydrate is dissolved in water, it forms a sol with potassium nitrate under the action of ammonia water, and further zirconium ions are converted into Zr(OH)4 precipitate; finally, after calcination treatment, Zr(OH)4 is sintered into ZrO2; during the calcination process, KNO3 is thermally decomposed to obtain K2O and is loaded on the surface of ZrO2 to form basic sites and used for catalyzing the ring - opening polymerization of ethylene oxide.
[0016] Preferably, in the step [S01], the acylating reagent is one of isobutyryl chloride, 3,3 - dimethylbutyryl chloride, and 2 - ethylbutyryl chloride; The mass - volume ratio of the use of the oligo - polyethylene glycol and the acylating reagent is 8 g:(0.4 - 0.5) ml.
[0017] By adopting the above technical solution, the acylating reagent can react with the terminal hydroxyl groups of oligo polyethylene glycol through a nucleophilic substitution reaction. Adding the acid-binding agent triethylamine can promote the forward progress of the substitution reaction; by adjusting the usage ratio of the reaction raw materials, making the oligo polyethylene glycol in excess in the substitution reaction can avoid the large generation of by-products.
[0018] Preferably, in the step [S02], the mass-volume ratio of the acylated polyethylene glycol, p-toluenesulfonyl chloride, phthalimide and hydrazine hydrate used is 1 g: (1 - 1.2) g: (0.2 - 0.3) g: (0.3 - 0.5) ml.
[0019] By adopting the above technical solution, the acylated polyethylene glycol continues to react with p-toluenesulfonyl chloride to introduce highly reactive sulfonate groups on the molecular chain. Then, through the nucleophilic substitution of phthalimide and the hydrazinolysis reaction of hydrazine hydrate, an amino structure is finally introduced at the end of the molecular chain of the acylated polyethylene glycol.
[0020] In the second aspect, the pre-hydrated bentonite impermeable material is prepared by the above preparation process in this application.
[0021] In summary, this application has the following beneficial effects: 1. By intercalation and treatment with organic composite components, this application improves the water absorption and water retention ability of calcium-based bentonite. After the intercalation of ethylene carbonate to expand the layer spacing, the organic composite component molecules enter the montmorillonite structural layers in the bentonite through the enlarged interlayer structure, adsorb on the montmorillonite layer walls, and capture water molecules through the molecular hydrophilic chain structure, improving the water absorption and water retention ability of the bentonite impermeable material.
[0022] 2. In this application, acylation modification is preferably adopted to introduce branched short-chain alkyl functional groups at the end of the oligo polyethylene glycol molecular chain. Through the steric hindrance effect, the migration resistance of the intercalated ethylene carbonate small molecules in the montmorillonite layer channels is increased, and the anti-elution ability of the intercalating agent small molecules is improved.
[0023] 3. The pre-hydrated bentonite impermeable material obtained by the preparation process of this application has a water absorption ratio ≥ 5.2 and a water retention rate ≥ 63.7%, and can greatly reduce the elution risk of the intercalating agent small molecules. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the test result of the water absorption and water retention performance of the pre-hydrated bentonite impermeable materials in Examples 1 - 4 and Comparative Examples 1 - 2 of this application.
[0025] Figure 2 This is the test result of the elution rate of the pre-hydrated bentonite impermeable materials in Examples 1 - 4 and Comparative Examples 1 - 2 of this application. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0026] The following are preparation examples of acylated polyethylene glycols: Preparation Example 1 Take 3 g of zirconium oxychloride octahydrate, 0.1 g of sodium hexametaphosphate and 0.5 g of potassium nitrate, mix them, add 50 ml of deionized water, adjust the magnetic stirring speed to 100 rpm, treat for 5 min, and then add ammonia water with a mass concentration of 14% at a rate of 0.5 ml / min until the pH of the system is 9.2. After standing overnight, filter to obtain the solid part. Dry it in an oven at 100 °C for 2 h, then place it in a tubular furnace, set the temperature to 450 °C, and calcine for 3 h to obtain the base catalyst.
[0027] Take 5 ml of ethylene glycol monomer, add 250 ml of deionized water and 0.2 g of the base catalyst, stir and treat for 5 min to obtain a mixed solution; then set the temperature to 45 °C, add the mixed solution to the reaction kettle at a rate of 4 ml / min. After complete addition, adjust the magnetic stirring speed to 150 rpm, mix and treat for 30 min, and then add 17.1 ml of ethylene oxide to the reaction kettle at a rate of 1 ml / min. Raise the temperature of the system to 100 °C under a nitrogen protection atmosphere, adjust the pressure to 2 MPa, treat for 6 min, slowly release the pressure of the reaction kettle to atmospheric pressure, adjust the pH of the system to 5 with 0.5 mol / L hydrochloric acid, then place the reaction kettle in a 4 °C cold water bath until the temperature of the system drops to 50 °C. Then add 500 ml of deionized water to the system, adjust the flow rate to 0.5 m / s, filter and elute with an ion exchange resin column. Dehydrate the eluted product under vacuum conditions at a temperature of 90 °C for 1 h, and then evaporate the remaining solvent at room temperature under a nitrogen atmosphere to obtain oligomeric polyethylene glycol.
[0028] Take 8 g of oligomeric polyethylene glycol, dissolve it in 75 ml of a mixed solvent, and then add 0.4 ml of isobutyryl chloride dropwise to the system at a rate of 0.1 ml / min. Adjust the magnetic stirring speed to 200 rpm and the temperature to 30 °C, and carry out light-shielding treatment for 6 h. Then set the vacuum degree to 0.01 MPa for vacuum filtration. Take the liquid phase part and add 0.1 mol / L potassium hydroxide to adjust the pH of the system to 7. Then add 50 ml of ice ether to the system, adjust the magnetic stirring speed to 200 rpm, treat for 5 min, and then filter to obtain the solid part. Redissolve it with 20 ml of dichloromethane and rotary evaporate at 45 °C for 2 h to obtain acylated polyethylene glycol.
[0029] Among them, the mixed solvent is obtained by mixing dimethyl sulfoxide and triethylamine in a volume ratio of 20:1.
[0030] Preparation Example 2 Take 3 g of zirconium oxychloride octahydrate, 0.3 g of sodium hexametaphosphate and 0.5 g of potassium nitrate, mix them, add 50 ml of deionized water, adjust the magnetic stirring speed to 100 rpm, treat for 20 min, then add ammonia water with a mass concentration of 14% at a rate of 0.5 ml / min until the pH of the system is 10. After standing overnight, filter to obtain the solid part. After drying in an oven at 120 °C for 3 h, place it in a tube furnace, set the temperature to 500 °C, and calcine for 4 h to obtain the base catalyst.
[0031] Take 5 ml of ethylene glycol monomer, add 250 ml of deionized water and 0.3 g of the base catalyst, stir and treat for 10 min to obtain a mixed solution; then set the temperature to 55 °C, add the mixed solution to the reaction kettle at a rate of 5 ml / min. After complete addition, adjust the magnetic stirring speed to 150 rpm, mix and treat for 45 min. Then add 18.4 ml of ethylene oxide to the reaction kettle at a rate of 2 ml / min. Under the protection of nitrogen atmosphere, raise the system temperature to 110 °C, adjust the pressure to 2.3 MPa, treat for 8 min, slowly release the pressure of the reaction kettle to atmospheric pressure, adjust the pH of the system to 6 with 0.5 mol / L hydrochloric acid, then place the reaction kettle in a 4 °C cold water bath until the system temperature drops to 50 °C. Then add 500 ml of deionized water to the system, adjust the flow rate to 0.5 m / s, filter and elute with an ion exchange resin column. Dehydrate the eluted product under vacuum conditions at a temperature of 100 °C for 2 h, and then evaporate the remaining solvent at room temperature under nitrogen atmosphere to obtain oligomeric polyethylene glycol.
[0032] All the other steps are the same as those in Preparation Example 1.
[0033] Preparation Example 3 Take 8 g of oligomeric polyethylene glycol, add 75 ml of a mixed solvent to dissolve it, then add 0.5 ml of 3,3-dimethylbutyryl chloride dropwise to the system at a rate of 0.1 ml / min, adjust the magnetic stirring speed to 220 rpm, the temperature to 35 °C, and perform light-shielding treatment for 7 h. Then set the vacuum degree to 0.02 MPa for vacuum filtration, take the liquid phase part and add 0.1 mol / L potassium hydroxide to adjust the pH of the system to 7. Then add 50 ml of ice ether to the system, adjust the magnetic stirring speed to 200 rpm, treat for 8 min, then filter to obtain the solid part, redissolve it with 20 ml of dichloromethane, and rotary evaporate at 45 °C for 2.5 h to obtain acylated polyethylene glycol.
[0034] Among them, the mixed solvent is obtained by mixing dimethyl sulfoxide and triethylamine in a volume ratio of 24:1.
[0035] All the other steps are the same as those in Preparation Example 1.
[0036] Preparation Example 4 Take 5 ml of ethylene glycol monomer, add 250 ml of deionized water and 0.25 g of base catalyst, stir for 8 min to obtain a mixed solution; then set the temperature at 50 °C, add the mixed solution to the reaction kettle at a rate of 4.5 ml / min. After complete addition, adjust the magnetic stirring speed to 150 rpm, mix for 40 min, then add 18 ml of ethylene oxide to the reaction kettle at a rate of 1.5 ml / min. Raise the system temperature to 105 °C under a nitrogen protection atmosphere, adjust the pressure to 2.2 MPa, and treat for 7 min. Subsequently, place the reaction kettle in a 4 °C cold water bath until the system temperature drops to 50 °C, slowly release the pressure of the reaction kettle to atmospheric pressure, then add 500 ml of deionized water to the system, adjust the flow rate to 0.5 m / s, filter and elute using an ion exchange resin column. Dehydrate the eluted product under vacuum conditions at a temperature of 95 °C for 1.5 h, and then evaporate the remaining solvent at room temperature under a nitrogen atmosphere to obtain oligomeric polyethylene glycol.
[0037] Take 8 g of oligomeric polyethylene glycol, dissolve it in 75 ml of mixed solvent, then add 0.4 ml of 2-ethylbutyryl chloride dropwise to the system at a rate of 0.1 ml / min, adjust the magnetic stirring speed to 200 rpm, the temperature to 30 °C, and carry out light-shielding treatment for 6 h. Then set the vacuum degree to 0.01 MPa for vacuum filtration. Take the liquid phase part and add 0.1 mol / L potassium hydroxide to adjust the pH of the system to 7. Then add 50 ml of ice ether to the system, adjust the magnetic stirring speed to 200 rpm, and treat for 5 min. Subsequently, filter to obtain the solid part, redissolve it with 20 ml of dichloromethane, and rotary evaporate at 45 °C for 2 h to obtain acylated polyethylene glycol.
[0038] Among them, the mixed solvent is obtained by mixing dimethyl sulfoxide and triethylamine in a volume ratio of 25:1.
[0039] The remaining steps are the same as those in Preparation Example 1.
[0040] Example 1 In this example, the preparation steps of the pre-hydrated bentonite impervious material are specifically as follows: Take 800 g of calcium-based bentonite, crush it and pass it through a 150-mesh sieve, then add deionized water at a water-to-material ratio of 1:10, adjust the stirring speed to 300 rpm, and treat for 10 min; then add sodium carbonate to adjust the pH of the system to 8, add 30 g of ethylene carbonate, set the temperature at 60 °C, stir at 75 rpm for 2 h, then add 50 g of organic composite component, continue to stir for 2 h, then filter to obtain the solid part and place it in a kneader, add 100 g of water glass, and knead at 50 °C for 1 h. Subsequently, use the kneaded material as the intermediate layer, flatten it with a roller and cover both sides with 120 g / m 2The needle-punched non-woven geotextile is subjected to a molding treatment under a pressure of 2 MPa by a flat vulcanizing machine to obtain an intermediate layer with an average thickness of 2 mm. Then, it is dried in a nitrogen atmosphere at 80 °C for 2 h and subsequently cooled overnight to obtain the product.
[0041] In this example, the preparation steps of the organic composite component are as follows: Take 10 g of acylated polyethylene glycol, add 50 ml of acetone and 10 ml of triethylamine, disperse for 3 min, then add 10 g of p-toluenesulfonyl chloride to the system, adjust the magnetic stirring speed to 100 rpm, treat for 3 h, then perform rotary evaporation at 45 °C for 2 h, let stand for 3 h, then dissolve the product in a mixed solution of 40 ml of dimethylformamide and 5 ml of absolute ethanol, add 2 g of phthalimide, adjust the magnetic stirring speed to 200 rpm, add 2 ml of 0.5 mol / L potassium hydroxide to the system under a nitrogen atmosphere, adjust the temperature to 60 °C, treat for 1 h, then raise the reaction temperature to 105 °C and continue to treat for 6 h. After that, evaporate the solvent under reduced pressure, add 75 ml of absolute ethanol and 3 ml of hydrazine hydrate to the system, reflux and react for 4 h, then evaporate the solvent under reduced pressure again, then add 30 ml of dichloromethane, filter the impurities, evaporate the solvent under reduced pressure again, then add 20 ml of absolute ether to the system, stir for 2 min, filter to obtain the precipitate, and dry it at 35 °C to obtain the organic composite component.
[0042] Among them, the calcium-based bentonite (montmorillonite 72 wt%) is provided by Shijiazhuang Borui Building Materials Co., Ltd.
[0043] In this example, the acylated polyethylene glycol is prepared according to Preparation Example 1.
[0044] Example 2 In this example, the preparation steps of the pre-hydrated bentonite impervious material are as follows: Take 850 g of calcium-based bentonite, crush it and pass it through a 150-mesh sieve, then add deionized water at a water-to-material ratio of 1:12, adjust the stirring speed to 350 rpm, and treat for 20 min; then add sodium carbonate to adjust the pH of the system to 9, then add 40 g of ethylene carbonate, set the temperature at 75 °C, stir and treat at 80 rpm for 3 h, then add 60 g of the organic composite component and continue to stir and treat for 2.5 h. Then filter to obtain the solid part and place it in a mixer, add 100 g of water glass, and perform mixing treatment at 65 °C for 1.5 h. Subsequently, use the mixed material as the intermediate layer, flatten it with a roller, and double-sided cover it with 120 g / m 2 The needle-punched non-woven geotextile is subjected to a molding treatment under a pressure of 3 MPa by a flat vulcanizing machine to obtain an intermediate layer with an average thickness of 2 mm. Then, it is dried in a nitrogen atmosphere at 90 °C for 2 h and subsequently cooled overnight to obtain the product.
[0045] In this example, the preparation steps of the organic composite component are as follows: Take 10 g of acylated polyethylene glycol, add 50 ml of acetone and 10 ml of triethylamine, disperse for 5 min, then add 11 g of p-toluenesulfonyl chloride to the system, adjust the magnetic stirring speed to 125 rpm, treat for 4 h, then rotary evaporate at 45 °C for 2 h, let stand for 3 h, and then add the product to a mixed solution of 40 ml of dimethylformamide and 5 ml of absolute ethanol to redissolve. Then add 3 g of phthalimide, adjust the magnetic stirring speed to 200 rpm, add 2 ml of 0.5 mol / L potassium hydroxide to the system under a nitrogen atmosphere, adjust the temperature to 60 °C, treat for 1.5 h, then raise the reaction temperature to 105 °C and continue to treat for 7 h. After that, evaporate the solvent under reduced pressure, add 75 ml of absolute ethanol and 4 ml of hydrazine hydrate to the system, reflux for 5 h and then evaporate the solvent under reduced pressure again. Then add 30 ml of dichloromethane, filter the impurities and then evaporate the solvent under reduced pressure again. Then add 20 ml of absolute ether to the system, stir for 3 min, filter to obtain the precipitate, and dry at 35 °C to obtain the organic composite component.
[0046] Among them, the calcium-based bentonite (montmorillonite 72 wt%) is provided by Shijiazhuang Borui Building Materials Co., Ltd.
[0047] In this example, the acylated polyethylene glycol is prepared from Preparation Example 2.
[0048] Example 3 In this example, the preparation steps of the pre-hydrated bentonite impervious material are as follows: Take 900 g of calcium-based bentonite, crush it and pass through a 150-mesh sieve, then add deionized water at a water-to-material ratio of 1:15, adjust the stirring speed to 500 rpm, and treat for 30 min; then add sodium carbonate to adjust the pH of the system to 9, add 50 g of ethylene carbonate, set the temperature at 80 °C, stir and treat at 100 rpm for 4 h, then add 80 g of the organic composite component, continue to stir and treat for 3 h, then filter to obtain the solid part and place it in a mixer, add 120 g of water glass, and mix and treat at 70 °C for 2 h. Then use the mixed material as the intermediate layer, flatten it with a roller and cover both sides with 120 g / m 2 Needled non-woven geotextile, and then press and treat it with a flat vulcanizing machine at 5 MPa to obtain an intermediate layer with an average thickness of 2 mm. Then dry it at 80 °C for 2 h under a nitrogen atmosphere, and then cool it overnight to obtain it.
[0049] In this example, the preparation steps of the organic composite component are as follows: Take 10 g of acylated polyethylene glycol, add 50 ml of acetone and 10 ml of triethylamine, disperse for 5 min, then add 12 g of p-toluenesulfonyl chloride to the system, adjust the magnetic stirring speed to 150 rpm, after treatment for 4 h, rotary evaporate at 45 °C for 2.5 h, let stand for 4 h, then add the product to a mixed solution of 40 ml of dimethylformamide and 5 ml of absolute ethanol to redissolve, add 3 g of phthalimide, adjust the magnetic stirring speed to 200 rpm, add 2 ml of 0.5 mol / L potassium hydroxide to the system under a nitrogen atmosphere, adjust the temperature to 60 °C, treat for 2 h, then raise the reaction temperature to 110 °C and continue to treat for 8 h, then evaporate the solvent under reduced pressure, add 75 ml of absolute ethanol and 5 ml of hydrazine hydrate to the system, reflux for 5 h and then evaporate the solvent under reduced pressure again, then add 30 ml of dichloromethane, filter the impurities and then evaporate the solvent under reduced pressure again, then add 20 ml of absolute ether to the system, stir for 3 min, filter to obtain the precipitate, and dry at 35 °C to obtain the organic composite component.
[0050] Among them, the calcium-based bentonite (montmorillonite 72 wt%) is provided by Shijiazhuang Borui Building Materials Co., Ltd.
[0051] In this example, the acylated polyethylene glycol is prepared from Preparation Example 3.
[0052] Example 4 The difference between this example and Example 1 is only that the acylated polyethylene glycol is prepared from Preparation Example 4.
[0053] Among them, the calcium-based bentonite (montmorillonite 72 wt%) is provided by Shijiazhuang Borui Building Materials Co., Ltd.
[0054] All the remaining steps are the same as those in Example 1.
[0055] Comparative Example 1 The difference between this comparative example and Example 1 is only that the preparation steps of the organic composite component are specifically as follows: Take 10 g of oligo polyethylene glycol, add 50 ml of acetone and 10 ml of triethylamine, disperse for 3 min, then add 10 g of p-toluenesulfonyl chloride to the system, adjust the magnetic stirring speed to 100 rpm, treat for 3 h, then rotary evaporate at 45 °C for 2 h, let stand for 3 h, then add the product to a mixed solution of 40 ml of dimethylformamide and 5 ml of absolute ethanol to redissolve, add 2 g of phthalimide, adjust the magnetic stirring speed to 200 rpm, add 2 ml of 0.5 mol / L potassium hydroxide to the system under a nitrogen atmosphere, adjust the temperature to 60 °C, treat for 1 h, then raise the reaction temperature to 105 °C and continue to treat for 6 h, then evaporate the solvent under reduced pressure, add 75 ml of absolute ethanol and 3 ml of hydrazine hydrate to the system, reflux for 4 h and then evaporate the solvent under reduced pressure again, then add 30 ml of dichloromethane, filter the impurities and then evaporate the solvent under reduced pressure again, then add 20 ml of absolute ether to the system, stir for 2 min, filter to obtain the precipitate, and dry at 35 °C to obtain the organic composite product.
[0056] All other steps are the same as in Example 1.
[0057] Comparative Example 2 The difference between this comparative example and Example 1 is only that an equal amount of polyethylene glycol is used instead of the organic composite component.
[0058] Among them, polyethylene glycol (model: PEG-6000) is provided by Shandong Yangdao Biotechnology Co., Ltd.
[0059] All other steps are the same as in Example 1.
[0060] Performance detection test Absorption and water retention performance test Take the pre-hydrated bentonite impervious materials of Examples 1-4 and Comparative Examples 1-2, cut them into test samples with a size of 20 cm × 25 cm respectively, record the mass of each group of test samples at this time, denoted as m1; prepare a test box of 60 cm × 49 cm × 34 cm, inject tap water until the water level line is 15 cm and then stop, then place each group of test samples in the test box respectively, take them out after standing for 3 h, then drain the water, record the mass of each group of test samples at this time, denoted as m2; then transfer them to an oven at 50 °C and dry for 4 h, record the mass of each group of test samples at this time, denoted as m3.
[0061] According to the formula: Water absorption ratio = (m2 - m1) / m1; Water retention rate = [(m3 - m1) / (m2 - m1)] × 100%.
[0062] Calculate the water absorption ratio and water retention rate of each group of test samples, and test each group of test samples 3 times and take the average value as the final data. The test results are as Figure 1 shown.
[0063] Elution rate test Take the pre-hydrated bentonite impermeable materials of Examples 1-4 and Comparative Examples 1-2, cut them into test discs with a diameter of 55 mm respectively, place them in a Buchner funnel with an inner diameter of 55 mm, and use tap water to perform elution treatment on the test discs at an injection rate of 5 ml / min. After the filtrate volume reaches 100 ml, recover the filtrate, change the injection rate to 20 ml / min to perform secondary elution on the test discs, and then maintain the injection rate. After eluting the test discs 10 times, collect the filtrate, and concentrate it at 90 °C for 2 h to obtain the concentrated filtrate.
[0064] Referring to HG / T 5391-2018, detect the ethylene carbonate content in the concentrated filtrates of Examples 1-4 and Comparative Examples 1-2, calculate the elution rate of ethylene carbonate in each group, and the test results are as Figure 2 shown.
[0065] Analyze Examples 1-4 and Comparative Examples 1-2 and combine with Figure 1 It can be seen that the water absorption and water retention test performances of the pre-hydrated bentonite impermeable materials prepared by the Example scheme are higher than those of the Comparative Example scheme, indicating that the Example scheme has more excellent water absorption and water locking capabilities. Among all the test groups, in the Comparative Example 1 scheme, the oligo polyethylene glycol was not acylated, and the combination of each raw material component did not significantly improve the water absorption and water locking properties of the material, but the overall water absorption and water retention effects were still better than those of Comparative Example 2.
[0066] Analyze Examples 1-4 and Comparative Examples 1-2 and combine with Figure 1-2 It can be seen that in terms of the elution rate, the Example scheme shows a change trend similar to the water absorption and water retention test data, indicating that while the Example scheme takes into account improving the water absorption and water retention properties of the material, it can also improve the anti-elution performance of the intercalating agent small molecules. Among all the groups, the ethylene carbonate elution in Comparative Example 2 is the most serious. This is because in Comparative Example 2, the molecular chain length of the high molecular weight polyethylene glycol is too large, and it is difficult to enter the montmorillonite interlayer of bentonite to play a role during the intercalation treatment stage. The small molecule intercalating agent ethylene carbonate is easily removed from the montmorillonite interlayer due to the scouring movement of water flow, ultimately resulting in a significant increase in the ethylene carbonate elution rate of the Comparative Example 2 scheme.
[0067] This specific embodiment is only an explanation of the present application, and it does not limit the present application. Those skilled in the art can make modifications to this embodiment without creative contributions according to needs after reading this specification, but as long as they are within the scope of the claims of the present application, they are protected by the patent law.
Claims
1. A preparation process of a pre-hydrated bentonite anti-seepage material, characterized in that It is obtained by mixing the following raw materials in parts by mass: 80-90 parts of calcium-based bentonite, 10-12 parts of binder, 5-8 parts of organic composite component, and 3-5 parts of ethylene carbonate; the preparation steps are as follows: Take calcium-based bentonite, crush it and then screen it, then add water for dispersion, adjust the pH, then add ethylene carbonate, raise the temperature and stir for treatment, then add the organic composite component and continue the treatment, then filter to obtain the solid part, add the binder, and then carry out mixing, film coating and then molding treatment, and obtain it after cooling; Among them, the preparation steps of the organic composite component are as follows: [S01] Take oligo-polyethylene glycol, dissolve it in a mixed solvent, then dropwise add an acylating reagent, react under light avoidance, then carry out reduced pressure filtration, take the liquid phase to adjust the pH, and carry out precipitation separation and rotary evaporation in sequence to obtain acylated polyethylene glycol; [S02] Take acylated polyethylene glycol, disperse it, then add p-toluenesulfonyl chloride, react and then carry out rotary evaporation, then dissolve it again, add phthalimide, dropwise add potassium hydroxide solution, raise the temperature for treatment, then remove the solvent, dissolve it again, add hydrazine hydrate, carry out reflux reaction, and obtain it after purification.
2. The preparation process of a pre-hydrated bentonite impervious material according to claim 1, characterized in that, The temperature-raising stirring treatment is: set the temperature at 60-80 °C, adjust the stirring speed to 75-100 rpm, and stir for 2-4 h.
3. The preparation process of a pre-hydrated bentonite impermeable material according to claim 1, characterized in that, In the step [S01], the preparation steps of oligo-polyethylene glycol include: take ethylene glycol monomer, dissolve it, then add an alkali catalyst, stir and mix and transfer it to a reaction kettle, then dropwise add ethylene oxide, pass nitrogen, raise the temperature for reaction, adjust the pH after pressure release, then lower the temperature, filter with an ion exchange resin, and dehydrate to obtain oligo-polyethylene glycol.
4. The preparation process of a pre-hydrated bentonite impervious material according to claim 3, characterized in that, The mass-volume ratio of the ethylene glycol monomer, alkali catalyst and ethylene oxide added is 5 ml: (0.2-0.3) g: (17.1-18.4) ml; the alkali catalyst is a supported K2O / ZrO2 catalyst.
5. The preparation process of a pre-hydrated bentonite impervious material according to claim 3, characterized in that, The temperature-raising reaction is: raise the system temperature to 100-110 °C, adjust the pressure to 2-2.3 MPa, and treat for 6-8 min.
6. The preparation process of a pre-hydrated bentonite anti-seepage material according to claim 1, characterized in that, In the step [S01], the mixed solvent is obtained by mixing dimethyl sulfoxide and triethylamine in a volume ratio of (20-25):
1.
7. The preparation process of a pre-hydrated bentonite impervious material according to claim 1, characterized in that, In the step [S01], the acylating reagent is one of isobutyryl chloride, 3,3-dimethylbutyryl chloride, and 2-ethylbutyryl chloride.
8. The preparation process of a pre-hydrated bentonite anti-seepage material according to claim 1, characterized in that, In the step [S01], the mass-volume ratio of oligo-polyethylene glycol and acylating reagent used is 8 g: (0.4-0.5) ml.
9. The preparation process of a pre-hydrated bentonite anti-seepage material according to claim 1, characterized in that, In the step [S02], the mass-volume ratio of acylated polyethylene glycol, p-toluenesulfonyl chloride, phthalimide and hydrazine hydrate used is 1 g: (1-1.2) g: (0.2-0.3) g: (0.3-0.5) ml.
10. A pre-hydrated bentonite anti-seepage material prepared by the preparation process according to any one of claims 1-9.
Citation Information
Patent Citations
Production method of organic / inorganic composite magnetic-carried suspending agent
CN105016860A
Modified bentonite impermeable material as well as preparation method and application thereof
CN112551944A
Technology for deeply removing heavy metal ions in wastewater by bentonite-based composite material
CN112607816A
Method for manufacturing modified-bentonite and modified-bentonite
KR101048436B1
Method of activation of clay and activated clay
US5573583A
Cited By
Green low-carbon C30 self-compacting concrete using dry-mixed mortar tail powder and preparation method of green low-carbon C30 self-compacting concrete
CN121537174A
Green low-carbon c30 self-compacting concrete using dry-mixed mortar tail powder and preparation method thereof
CN121537174B
